1997
DOI: 10.1097/00005392-199706000-00021
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Urine Cytology for Diagnosing Bladder Cancer in Spinal Cord Injured Patients

Abstract: The high sensitivity and specificity of multiple cytology studies in this population suggest that cytology is a useful adjunct to improve the detection of bladder cancer in spinal cord injured patients with chronic (longer than 5 years) indwelling catheters. We recommend a minimum of yearly cytology in all high risk spinal cord injured patients with subsequent biopsies in all patients with any suspicious finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The aim of long-term bladder rehabilitation of SCI patients, including yearly cytology and biopsies, is the prevention of bladder infections and avoidance of urinary complications. 3 In our series there was no signi®cant statistical dierence between the number of infections, the period since the injury, the neurologic level of the spinal cord lesion and the histopathology. These results show that none of these variables have aected the histopathological in¯ammation type.…”
Section: Discussionmentioning
confidence: 45%
“…The aim of long-term bladder rehabilitation of SCI patients, including yearly cytology and biopsies, is the prevention of bladder infections and avoidance of urinary complications. 3 In our series there was no signi®cant statistical dierence between the number of infections, the period since the injury, the neurologic level of the spinal cord lesion and the histopathology. These results show that none of these variables have aected the histopathological in¯ammation type.…”
Section: Discussionmentioning
confidence: 45%
“…21 The prevailing belief is that indwelling catheters, particularly when used for 410 years, are a risk factor for bladder cancer. [28][29][30] Most series of SCI patients with bladder cancer show that a high proportion used indwelling catheters (50-100%). 4,7,9,10,13,[16][17][18] Data from the US National Spinal Cord Injury Database suggest that although intermittent catheterization has increased in popularity since the 1970s, few patients continue to use it over long-term follow-up, whereas patients who use an indwelling catheter are likely to continue to use this strategy long term.…”
Section: Risk Factors For Development Of Bladder Cancer In Sci Patientsmentioning
confidence: 99%
“…Urinalysis has been studied as a screening tool among older males in the general population; 36 however, its usefulness in the SCI population is limited because of the difficulty in interpreting the results in SCI patients (because of chronic bacteriuria and hematuria from catheter use). Stonehill et al 30 sought to determine the effectiveness of urine cytology at detecting bladder cancer in SCI patients. Two hundred and eight SCI patients (primarily managed with indwelling catheters) had urine cytologies analyzed, and then bladder biopsies performed.…”
Section: Risk Factors For Development Of Bladder Cancer In Sci Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine cytology has been used in screening for bladder cancer in cohorts of men exposed to occupational bladder carcinogens, but did not have a clinical impact on the development of cancer. 13 A recent study by Stonehill advocates the use of cytology for screening SCI patients, 14 whereas other reports have shown that it is not adequately speci®c due to concurrent in¯ammation from infection and catheterization. 2,15 In recent years, several assays have been introduced as screening mechanisms for recurrent bladder cancer, though none have been indicated for populations at risk without a prior bladder cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%